Forestry Professional Values (FPVs) as Perceived by In-Service Syrian & French Forest Engineers (Damascus University Journal of educational and Psychologyical sciences, 2021)
AbstractProfessional values play, along with related knowledge and skills, a labeling role for a given career’ community members. Keeping in mind the real competitive nature of work market, having possession of professional values could mean among other things job-opportunities. This fact promotes educational institutions to enhance their efforts to improve their professional outputs. Within this context, forestry educational institutions are also forced to look for the best ways to provide forestry sector with well qualified and high level trained staffs. But the challenge in the educational forestry sector is multifaceted; forest engineer has not only to be able to satisfy work market’ constraints but also to be able to deal with emergent and non-predictable defies in forests and natural milieus; Unfortunately, forestry professional value could not yet be integrated within curricula because they are still implicit for most foresters. Along with this framework, This paper tries to make a step towards the didactic translation of in-service forest engineers’ acts and behaviors into standard forestry professional values (FPVs). The targeted population of this study composed of Syrian and French forest engineers who   work in a common forestry project. Through this paper, fourteen FPVs have been identified and classified within three levels in addition to the schematization of two professional ethos identity models. The findings have included also probable educational assets.
Keywords: Forestry; career